Performance of Slab-on-Pile and Embankment Foundations in Soft Clay under Subsidence Conditions: A Case Study from Northern Java - Setiawan, Yoga; Fathani, Teuku Faisal (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2025)
The northern coast of Java is a critical economic corridor in Indonesia but faces severe geotechnical and environmental challenges, including erosion, flooding, and land subsidence. In the Semarang–Demak Plain, land subsidence is a major concern due to thick, compressible clay deposits and shallow groundwater, which pose significant risks to infrastructure stability. The Semarang–Demak Toll Road, connecting Semarang City and Demak Regency, was constructed using two foundation systems: slab-on-pile and embankment with prefabricated vertical drains (PVD). At the interchange between Pantura Road and the toll road, a slab-on-pile foundation was selected to address high settlement risks. This study evaluates and compares the performance of both foundation types using one-dimensional analysis and two-dimensional finite element analysis (FEA). The results show that the slab-on-pile system experienced settlements of 0.519 m (one-dimensional analysis) and 0.775 m (FEA), while the embankment with PVD resulted in significantly higher settlements of 2.533 m (one-dimensional analysis) and 1.038 m (FEA). The slab-on-pile foundation also achieved a shorter consolidation period and a higher safety factor. These findings confirm the effectiveness of the slab-on-pile system in minimising settlement and improving long-term performance under challenging soil conditions. The study underscores the importance of selecting appropriate foundation strategies in subsidence-prone coastal areas and provides practical insights for infrastructure planning and geotechnical design in similar environments.